2004
DOI: 10.1073/pnas.0405426101
|View full text |Cite
|
Sign up to set email alerts
|

129Xe on Ir(111): NMR study of xenon on a metal single crystal surface

Abstract: NMR experiments of 129 Xe adsorbed on an iridium single crystal surface are reported. Very high nuclear polarization (P z Ϸ 0.7) makes the experiment possible. A coverage of less then one monolayer is investigated on the Ir(111) surface with an area of 0.8 cm 2 . The observed resonance line shifts are very large and highly anisotropic. We find iso ‫؍‬ 1,032 ؎ 11 ppm and an ‫؍‬ 291 ؎ 33 ppm, which are far above the typical range of physisorption. The highly ordered substrate leads to homogeneous conditions for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
14
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 38 publications
3
14
0
Order By: Relevance
“…Interestingly, we found that, in contrast to the behavior of He atom in PuO 2 , there does exist some amount of charge transfer and chemical bonding between Xe and PuO 2 , which is in reasonable agreement with recent findings regarding the chemical interactions of RG-metal systems, including RG-actinide materials. [39][40][41][42] However, apart from O 2 and RG, there often exist other impurity atoms, as addressed above, and these impurities could also significantly alter the material properties of PuO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, we found that, in contrast to the behavior of He atom in PuO 2 , there does exist some amount of charge transfer and chemical bonding between Xe and PuO 2 , which is in reasonable agreement with recent findings regarding the chemical interactions of RG-metal systems, including RG-actinide materials. [39][40][41][42] However, apart from O 2 and RG, there often exist other impurity atoms, as addressed above, and these impurities could also significantly alter the material properties of PuO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…15,4547 However, it has been biomedical applications that have largely driven the development of hyperpolarized MR techniques over the past decade; indeed, for gas imaging in particular, HP 129 Xe can be used to assess lung function and report on functional and microstructural abnormalities. 6,4850 A useful figure of merit for 129 Xe hyperpolarizers is the total 129 Xe magnetization, M Xe , delivered in a clinically useful gas volume, typically ∼0.5–1 L at 760 Torr.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] with HP 129 Xe is of particular interest. Moreover, xenon is soluble in blood (6), other tissues (7,8), and many biologically compatible liquids (9), and its proclivity for interacting with other substances and its wide chemical shift range make HP 129 Xe a sensitive NMR probe of molecular and material surfaces (1,(10)(11)(12). In many applications, HP 129 Xe can replace 3 He, and the relative abundance of 129 Xe can greatly reduce the impact of the worldwide 3 He shortage (13) in these instances.…”
mentioning
confidence: 99%
“…Moreover, xenon is soluble in blood (6), other tissues (7, 8), and many biologically compatible liquids (9), and its proclivity for interacting with other substances and its wide chemical shift range make HP 129 Xe a sensitive NMR probe of molecular and material surfaces (1,(10)(11)(12) Xe is usually created via spin-exchange optical pumping (SEOP) (23), whereby the unpaired electronic spins of an alkali metal vapor (e.g., Rb) are polarized via optical pumping with circularly polarized light, and the polarization is transferred to noble gas nuclear spins during collisions. It is generally anticipated that high P Xe is achievable only in the low xenon-density regime (18, 24), because (i) higher Xe densities increase the destruction of Rb polarization from nonspin-conserving collisions at a rate that is orders of magnitude worse than those of other gases like N 2 and He (25-27); and (ii) higher total pressures tend to quench the threebody van der Waals contribution to Rb-Xe spin exchange-leaving the less-efficient two-body term (18,23).…”
mentioning
confidence: 99%